2020
DOI: 10.1101/2020.07.31.20161216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and Safety of a SARS-CoV-2 Inactivated Vaccine in Healthy Adults Aged 18-59 years: Report of the Randomized, Double-blind, and Placebo-controlled Phase 2 Clinical Trial

Abstract: BACKGROUND The top priority for the control of COVID-19 pandemic currently is the development of a vaccine. A phase 2 trial conducted to further evaluate the immunogenicity and safety of a SARS-CoV-2 inactivated vaccine (CoronaVac). METHODS We conducted a randomized, double-blind, placebo-controlled trial to evaluate the optimal dose, immunogenicity and safety of the CoronaVac. A total of 600 healthy adults aged 18-59 years were randomly assigned to receive 2 injections of the trial vaccine at a dose of 3 μg/0… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 14 publications
6
82
3
6
Order By: Relevance
“…They can be produced relatively easily, however, their yield might be limited by productivity of virus in cell culture and the requirement for biosafety level 3 (BSL3) production facilities. Examples are Corona-Vac (initially called PiCoVacc), developed by Sinovac Biotech Ltd. in China 34,35 (discussed below) as well as several other candidates developed in China, by Bharat Biotech in India and by the Research Institute for Biological Safety Problems in Kazakhstan. These vaccines are usually administered intramuscular and might be adjuvanted with alum or other adjuvants.…”
Section: Inactivated Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be produced relatively easily, however, their yield might be limited by productivity of virus in cell culture and the requirement for biosafety level 3 (BSL3) production facilities. Examples are Corona-Vac (initially called PiCoVacc), developed by Sinovac Biotech Ltd. in China 34,35 (discussed below) as well as several other candidates developed in China, by Bharat Biotech in India and by the Research Institute for Biological Safety Problems in Kazakhstan. These vaccines are usually administered intramuscular and might be adjuvanted with alum or other adjuvants.…”
Section: Inactivated Vaccinesmentioning
confidence: 99%
“…Sinovac very recently reported results from a randomized, double blinded placebo controlled Phase II trial (NCT04352608) with their inactivated vaccine (Figure 3c) CoronaVac (the name PiCoVacc was used in the manuscript describing the NHP results, Table 1) in 600 healthy adults (18-59 years of age) 35 . They used two doses, 3 ug or 6 ug, adjuvanted with aluminium hydroxide in a 2 week or 4 week prime-boost regimen.…”
Section: Sinovac's Coronavacmentioning
confidence: 99%
“…27 The inactivated SARS-CoV-2 vaccine containing aluminum hydroxide developed by Sinovac has entered phase 3 clinical trials, with results from the phase 2 trial demonstrating that two doses of 6 μg/0.5 mL or 3 μg/0.5 mL of the vaccine were well-tolerated and immunogenic in healthy adults (Table 1). 43 Phase 2 trial results of the inactivated SARS-CoV-2 vaccine, constructed by Wuhan Institute of Biological Products and Sinopharm, reported that the geometric mean titers (GMT) of NAbs were 121 and 247 at day 14 after 2 injections in participants receiving vaccine on days 0 and 14 and on days 0 and 21, respectively, displaying only transient and self-limiting adverse reactions. 44 Viral RNA Fig.…”
Section: The Development Of Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…The safety profile of the vaccine was excellent and both doses were comparable to placebo1. 100 No grade 3 adverse reactions were reported. The phase-III trials in adults and the elderly are underway.…”
Section: Clinical Trial Resultsmentioning
confidence: 99%